Efikasi Diri, Dukungan Sosial, dan Self-Care Management Klien Hipertensi - Susanti, Sofy Norma; Sukarmin, Sukarmin; Jauhar, Muhamad; Tiara, Novi; Lasmini, Lasmini (Jurnal Ilmiah Ners Indonesia, 2024)
A serious illness that can raise morbidity and death rates is hypertension. Unhealthy habits contribute to many health issues and are one of the main causes of disease. Patients' inadequate self-care behaviors lead to disease consequences. This results from a demand for increased social support and self-assurance. This study examines the connection among hypertension patients' self-efficacy social support, self-care management, and social support. Correlation analytics is used in the research design using a cross-sectional methodology. Purposive sampling was used to get a sample of 44 responders. Being over eighteen, having a hypertension diagnosis, and being literate in writing and collaborative work were requirements for inclusion. The General Presieved Self-Efficacy Scale, Social Support RAND Health, and Self-Care Management (a modified method of assessing African Americans' self-care behaviors and blood pressure knowledge) were the research instruments utilized. The chi-square and odds ratio (OR) tests were utilized in the data analysis. Self-efficacy (p=0.003; 0R=7.667) and social support (p=0.004; OR=7.219) were found to be statistically significantly correlated with self-care management in hypertension patients. For hypertension patients, social support and high self-efficacy can enhance self-care management, allowing blood pressure control and preventing problems. The results of the research are the basis for nurses in developing interventions to improve hypertension self-care management through managing self-efficacy and social support. Abstrak Hipertensi adalah penyakit yang berpotensi meningkatkan morbiditas dan mortalitas. Gaya hidup yang tidak sehat menjadi penyebab utama penyakit, yang menyebabkan beberapa masalah. Perilaku perawatan diri yang buruk pada klien menyebabkan komplikasi penyakit. Dukungan sosial dan kepercayaan diri yang rendah adalah penyebabnya. Tujuan penelitian ini adalah menganalisis dukungan sosial dan efikasi diri berkorelasi dengan manajemen perawatan diri pasien hipertensi. Penelitian ini dirancang dengan menggunakan analitik korelasi dan metode cross-sectional. Metode purposive sampling digunakan untuk mengumpulkan sampel dari 44 orang yang menjawab. Mereka yang diterima berusia minimal 18 tahun dan memiliki kemampuan membaca, menulis, dan bekerja sama. Instrument penelitian menggunkan kuesioner efikasi diri (General presieved self-efficacy scale), dukungan sosial (Social support RAND Health), dan self care management (modifikasi dari measuring blood pressure knowledge and self-care behaviors of African Americans). Analisis data menggunakan uji chi square dengan uji odds ratio (OR). Hasil penelitian menunjukkan terdapat hubungan yang signifikan secara statistic antara efikasi diri (p=0,003; OR=7,667) dan dukungan sosial (p=0,004; OR=7,219) dengan self care menagament pada klien hipertensi. Efikasi diri dan dukungan sosial yang baik dapat meningkatkan self care management pada klien hipertensi sehingga tekanan darah dapat terkontrol dan mencegah komplikasi. Hasil penelitian menjadi dasar perawat dalam mengembangkan intervensi peningkatkan manajemen perawatan diri hipertensi melalui pengelolaan efikasi diri dan dukungan social. Kata Kunci: Dukungan sosial, efikasi diri, hipertensi, self care management